Genetic risk factors and genomic signatures in Sub-Saharan African Breast Cancer : a multifaceted study - (:unkn) unknown (My University, 2024)
"Breast cancer is a prevalent global health concern, with substantial morbidity and mortality rates.Despite advancements in diagnostics and therapeutics, addressing breast cancer remains a critical challenge. The EpiMaCT laboratory has embarked on comprehensive public health initiatives in low- and middle-income countries to enhance healthcare access and understand the epidemiology of chronic diseases.In Sub-Saharan Africa, the burden of breast cancer is intensified by endemic infectious diseases and the increasing prevalence of non-communicable diseases. Alarmingly high mortality rates reflect a dire prognosis, characterized by a predominant triple-negative molecular aggressive subtype and early age of diagnosis. Our pioneering epidemiological study in Benin unveiled these trends, corroborated by a subsequent meta-analysis across Sub-Saharan Africa.My project aims to unravel the genetic landscape of breast cancer in Benin, Togo, and Gabon, focusing on identifying genomic signatures distinguishing its pathogenesis and discovering new therapeutic targets. Our study represents a significant advancement in genomics in these countries, being the first of its kind in the region, thus marking an innovative approach. By exploring links between these mutations and patient survival, our prospective and retrospective approach offers a comprehensive view of the disease, paving the way for significant advances in its management."
Keywords: African Research